2013
DOI: 10.4321/s0004-05922013000100012
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos ambientais e genéticos sobre escores visuais e ganho em peso ao sobreano de bovinos Brangus

Abstract: RESUMOO objetivo do presente trabalho foi estudar os efeitos da idade da vaca ao parto (IVP) e idade do animal ao sobreano (IDS), bem como os efeitos genéticos aditivos diretos (AD) e maternos (AM) e da heterozigose individual (HI), sobre os escores visuais de conformação (CS), precocidade (PS) e musculatura (MS) ao sobreano e o ganho médio diário de peso da desmama ao sobreano (GDS) de animais formadores da raça Brangus. Foram analisados 24 531, 21 166, 24 006 e 25 419 dados de CS, PS, MS e GDS, respectivamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
3
0
2
Order By: Relevance
“…Regarding age of dams at calving, previous studies have reported its significant linear and quadratic effects on WW (Santos et al, 2011;Szabó et al, 2012;Chud et al, 2014;Goldberg and Ravagnolo, 2015), corroborating the results found in the current study (P<0.01). In addition, Queiroz et al (2013) found significant linear and quadratic effects of age of dam on YW gain in a Brangus cattle population, showing the influence of this parameter on the performance of calves after the weaning period. Similarly, in the current study, significant linear effect of age of dam at calving was found for YW (P<0.01), which can be interpreted as a residual effect of this source of variation, since the animal performance after weaning may be connected to the expression of its own genetic potential for growth.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Regarding age of dams at calving, previous studies have reported its significant linear and quadratic effects on WW (Santos et al, 2011;Szabó et al, 2012;Chud et al, 2014;Goldberg and Ravagnolo, 2015), corroborating the results found in the current study (P<0.01). In addition, Queiroz et al (2013) found significant linear and quadratic effects of age of dam on YW gain in a Brangus cattle population, showing the influence of this parameter on the performance of calves after the weaning period. Similarly, in the current study, significant linear effect of age of dam at calving was found for YW (P<0.01), which can be interpreted as a residual effect of this source of variation, since the animal performance after weaning may be connected to the expression of its own genetic potential for growth.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, heterozygosity, which represents the proportion of heterozygote genotypes in the population, may be a useful indicator and has been often used to evaluate the degree of heterosis (Akanno et al, 2018;Iversen et al, 2019;Prastowo et al, 2021). According to Queiroz et al (2013), heterozygosity has a significant effect on performance traits in Brangus animals and its inclusion in the model may improve prediction accuracy (Raidan et al, 2018). Therefore, heterozygosity should be included in models for estimation of genetic parameters and breeding values of crossbred animals (Schiermiester et al, 2015;Raidan et al, 2018;Iversen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A seleção de animais com base nas características de desenvolvimento ponderal e ganho de peso é utilizada há muitos anos (QUEIROZ et al 2013). No entanto, a implantação dessas características pode levar à seleção de animais de maior porte e com baixa eficiência alimentar (GOMES et al, 2012), sendo considerados animais tardios, ou seja, que entram mais tarde em puberdade e produzem menos carne.…”
Section: Introductionunclassified
“…In livestock, the constant improvement of genetic potential is an important factor for increasing productivity, improving performance parameters and quality of the final product (Montaldo et al 2012). In Brazil, the selection of beef cattle is based mainly on using standardized weights at different ages and weight gains (Queiroz et al 2013). However, the selection of animals with a phenotype suitable for the production system is a key aspect of increasing the economic efficiency of a rural enterprise (Faria et al 2009).…”
Section: Introductionmentioning
confidence: 99%